Penyuluhan Baby Massage untuk Meningkatkan Pengetahuan Ibu pada Komunitas Batita usia 3-18 Bulan di Desa Candirenggo Kecamatan Singosari - Winda Rahmawati Marupa; Rakhmad Rosadi; Ratna Vidya Amelia (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
The growth period during toddlerhood is a very important period, where every process of child growth and development takes place naturally. One way to optimize children's growth and development is by providing stimulation. One of them is by giving massage. This counseling was conducted with the aim of increasing the mother's knowledge related to how to give massage to babies so that it can provide optimal benefits related to child growth and development. The media used is leaflet media distributed to all counseling participants containing definitions, what not to do, and recommended times for doing baby massage with 20 participants. The evaluation results of this counseling showed an increase in knowledge for mothers.